Modelling of Al impurity in perovskite and ilmenite structures of MgSiO3 - Stashans, A. (2009)
A methodology based on the Hartree-Fock theory is used to study pure MgSiO3 crystals as well as Al doping in perovskite and ilmenite modifications of this mineral. Atomic displacements in the neighbourhood of the defect are obtained for cases when the Al substitutes for either Mg or Si host atoms. The atomic relaxation is due to the changes produced upon the chemical bonding within the defective region and in some occasions obeys the Coulomb electrostatic interaction. Band structure properties are briefly revised for the pure and doped minerals. The occurrence of Al-bound hole polaron is predicted in the ilmenite mineral. The results of output are compared to the available reports on the same subject in both experimental and theoretical fields of the investigation. © Springer-Verlag 2009.